2023
DOI: 10.1007/s13592-023-01018-8
|View full text |Cite
|
Sign up to set email alerts
|

Stingless bee (Tetragonula carbonaria) foragers prioritise resin and reduce pollen foraging after hive splitting

Abstract: Stingless bees are increasingly in demand as pollinators in agricultural crops within the tropics and subtropics. Hive splitting, where one strong managed hive is “split” into two independent daughter colonies, is commonly used to increase hive numbers. However, how splitting impacts foraging behaviour or the time taken for the colony to recover from splitting has not previously been studied. We assessed the impact of splitting on the foraging behaviour of Tetragonula carbonaria colonies. The number of returni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Additional limitations of our study are the limited number of observed colonies per species and that all observations were conducted in a single season. Environmental and colony‐specific factors, such as predator pressure, a colony's developmental or feeding stage, time of day, and season, affect resource collection and resource intake by colonies, including resin collection (Hilário et al., 2000, 2012; Hofstede & Sommeijer, 2006; Leonhardt & Blüthgen, 2009; Newis et al., 2023; Nunes‐Silva et al., 2010; Shanahan & Spivak, 2021). To fully elucidate the effect of resin collection on stingless bee foraging and resource intake, repeated observations across different times of the year and including additional colonies as well as controlled experiments that manipulate resin and pollen storage within nests (e.g., Newis et al., 2023) are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations of our study are the limited number of observed colonies per species and that all observations were conducted in a single season. Environmental and colony‐specific factors, such as predator pressure, a colony's developmental or feeding stage, time of day, and season, affect resource collection and resource intake by colonies, including resin collection (Hilário et al., 2000, 2012; Hofstede & Sommeijer, 2006; Leonhardt & Blüthgen, 2009; Newis et al., 2023; Nunes‐Silva et al., 2010; Shanahan & Spivak, 2021). To fully elucidate the effect of resin collection on stingless bee foraging and resource intake, repeated observations across different times of the year and including additional colonies as well as controlled experiments that manipulate resin and pollen storage within nests (e.g., Newis et al., 2023) are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini akan meningkatkan produksi madu dan hasil penyerbukan secara lebih cepat, yang akan meningkatkan hasil pertanian dan keberlanjutan ekosistem. Teknik splitting juga efektif untuk menghindari eksploitasi populasi lebah di alam, karena teknik ini mampu memecah satu koloni induk menjadi dua hingga tiga koloni baru (Newis et al, 2023;Riendriasari et al, 2023). Teknik splitting juga menguntungkan bagi peternak karena jumlah koloni yang lebih cepat bertambah.…”
Section: Pendahuluanunclassified